Achieving purple light excitable high-efficiency temperature-responsive dual- and single-mode afterglow in carbon dots. (May 2023) - Gao, Jingran; Wu, Xiulan; Jiang, Xin; Li, Ming; He, Rongxing; Shen, Wei
Abstract: Afterglow materials including thermally activated delayed fluorescence (TADF) and room temperature phosphorescence (RTP) have inspired extensive attention and research in anti-counterfeiting and sensing application prospects. However, a critical challenge currently remains within this afterglow materials only exhibit single-mode phosphorescence or delayed fluorescence with a persistent luminescence but low quantum yield. In this study, carbon dots composites with long-lived afterglow and ultra-high afterglow quantum yields of 193.5 ms and 35.07% were obtained by embedding the luminescent centers of ciprofloxacin into the formed rigid boric acid matrix by a one-step hydrothermal with purple light as the excitation wavelength. It is worth mentioning that the constructed composites exhibit dual-mode afterglow (DF and RTP) features at room temperature. Moreover, the carbon dots composites have distinctive temperature-responsive color-tunable properties and represent afterglow emission dominated by delayed fluorescence or phosphorescence at different temperatures. Based on the extraordinary temperature sensitivity, a single-mode ultra-long phosphorescence with a lifetime of up to 1.11 s is achieved at low temperatures. Additionally, as-prepared carbon dots composites exhibit the afterglow quantum yield of 40.97% in CB-VII, which is an ultra-high value for inorganic non-metallic materials. Furthermore, the resultant composites of carbon dots with new potential materials of encryption technology are designed for advanced information encryption and anti-counterfeiting applications. Graphical abstract: Carbon dots composites with long-lived afterglow and ultra-high afterglow quantum yields of 193.5 ms and 35.07% were obtained by embedding the luminescent centers of ciprofloxacin into the formed rigid boric acid matrix by a one-step hydrothermal with purple light as the excitation wavelength. The materials possesses distinctive afterglow emission dominated by delayed fluorescence or room temperature phosphorescence at different temperatures and enables color-tunable afterglow emission with temperature-sensitivity. Image 1